1079. When Does a Trans-Esophageal Echocardiogram (TEE) Change Management of Staphylococcus aureus Bacteremia (SAB)?. (26th November 2018) - Lam, John; Robinson, Stephen; Gregson, Daniel; Somayaji, Ranjani; Conly, John; Welikovitch, Lisa; Parkins, Michael
Abstract: Background: The recognition of infective endocarditis (IE) as a serious complication of SAB has led to a low threshold for echocardiography, extended treatment (eTx) with anti-staphylococcal agents (anti-SA), and even surgery. However, indications for eTx outside of IE are numerous. We sought to determine the frequency in which findings from a TEE changed clinical SAB management. Methods: Adults with SAB within the Calgary Health Zone between 2012 and 2014 were included if both a transthoracic echocardiogram (TTE) and TEE were performed within 7 days of each other. Patients potentially benefiting from eTx courses were a priori defined as having ≥1 of; (1) metastatic phenomena, (2) complicated SAB (defined as community acquired (CA), persistent fever/bacteremia at ≥48 hours), (3) intracardiac devices, and/or (4) Duke criteria defined IE (separately evaluated using TTE or TEE). Patient demographics, treatment (including changes to anti-SA duration and surgical indications), and clinical outcomes were extracted and evaluated. Results: Of 961 SAB episodes, 179 (18% MRSA) met inclusion criteria (median 3.0 days, IQR 1.9–5.1 between TTE and TEE). Within the cohort 29% ( n = 51) had metastatic phenomena (intracranial; 9% [ n = 16], vertebral; 8% [ n = 14]; empyema; 6% [ n = 11]). Complicated bacteremia was present in 89% ( n = 159), while 13% ( n = 23) had intravascular hardware (39% pacemakers, 65% valve prostheses). IE was diagnosed in 22% ( n = 40) of SAB episodes, with TTE identifying 58% of vegetations ( n = 23) and TEE identifying an additional 30% ( n = 15). Of the cohort, 89% ( n = 160), 37% ( n = 67), 4% ( n = 7) of SAB had ≥1, 2, and 3 nonechocardiographic indications for eTx, respectively. Only one patient met criteria for eTx solely based on IE diagnosed from concordant TTE and TEE. Actual duration of therapy did not differ in SAB episodes that had ≥1 a priori eTx criteria but had a negative TEE relative to those who had a positive TEE (36.7 days, IQR 23.4–48.6 vs. 43.8 days, IQR 33.3–49.5, P = 0.17). Of the 15 episodes of TEE-only evident IE, 14 were CA, 12 had prolonged BSI, and nine embolic phenomena. Only 11 patients in the cohort required cardiac surgery, none were identified exclusively by TEE. Conclusion: Routine performance of TEE may not be required in all SAB as many patients have alternate indications for eTx with anti-SA regardless of TEE findings. Disclosures: All authors: No reported disclosures.